Pemberdayaan Ekonomi Masyarakat Melalui Pengelolaan Wisata Syariah : (Studi Kasus Wisata Syariah Telaga Biru Desa Lempong Kecamatan Bola Kabupaten Wajo) - Gusnia; Nurlaelah Abbas; Asni Djamereng (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to determine community empowerment efforts through the management of Telaga Biru Sharia Tourism and to find out the form of community economic business in the management of Telaga Biru Sharia Tourism in Lempong Village, Bola District, Wajo Regency. In explaining this journal, the type of research is descriptive qualitative using a sociological approach method. Primary data sources obtained based on the results of informant interviews and secondary data sources collected through relevant books and documents. Observation, interviews, and documentation as data collection methods used. Data management and analysis techniques are carried out through three stages, namely: data reduction, data presentation (display data), and conclusion drawing. The results of this study are that there are two community empowerment efforts through the management of Telaga Biru Sharia Tourism, namely: 1) Recruiting local residents as labor 2) Provision of facilities to support community economic activities. The form of community economic business in the management of Telaga Biru Sharia Tourism is 1) Culinary Business 2) Souvenir business 3) Buoy rental service business around Telaga Biru Sharia Tourism